MENANAM DAN MENJUAL JAGUNG DEMI BERAS: PENGARUH PERUBAHAN KONSUMSI MAKANAN POKOK PADA KOMUNITAS ADAT JALAWASTU - Kurnianto, Danu (Studi Budaya Nusantara, 2024)
The Jalawastu traditional community has had a culture of food security for centuries with white corn as the variety they cultivate for staple food. Today's reality shows that hybrid corn is a variety that has been commodified as the main agricultural product. People's behavior, on the other hand, shows that corn is now not the main choice as their staple food. The Jalawastu traditional community now uses rice as their main daily food rather than corn. Based on field research conducted in 2022, this article was prepared by analyzing several factors that have brought about economic and socio-cultural changes that have occurred over the last few decades in the Jalawastu Traditional Village. The influence of the market economy on agriculture in Jalawastu is allegedly strong in bringing about changes in their way of life and outlook on life that has actually been regulated through customary mechanisms. Apart from that, this article tries to raise any threats in realizing the food security and sovereignty of indigenous communities in Jalawastu. In the end, the author concludes that there are still efforts towards food sovereignty based on their traditional livelihood system even though there is a knowledge gap between generations regarding the symbolic value of corn